Understanding the social–ecological systems of non-state seafood sustainability scheme in the blue economy - Isa Olalekan Elegbede; Kafayat A. Fakoya; Morenike A. Adewolu; Toheeb Lekan Jolaosho; Joseph Adewale Adebayo; Esther Oshodi; Ruth Funmilola Hungevu; Amos Olayinka Oladosu; Oluwatoyosi Abikoye (Environment, Development and Sustainability, 2023)
Non-state sustainability initiatives, such as eco-certification and voluntary sustainability standards, are eco-friendly, market-driven, and privately managed initiatives that garner support from concerned stakeholders in the blue economy. Consequently, these initiatives play pivotal roles in enhancing resource sustainability within the seafood sector. However, despite their importance, the intricacies of how non-state seafood sustainability schemes operate within the blue economy remain unclear. Therefore, this study examines the interactions of these non-state actors within institutional, social, and ecological contexts to improve common resource management. This study is based on a comprehensive review of secondary data from the literature to delineate its scope. In recent years, there has been an increase in non-state initiatives advocating for sustainable fisheries and the sustainable use of natural blue resources. These initiatives claimed to exhibit established institutional, social, and ecological synergies, yet the foundational principles guiding them remain underexplored. It is essential to note that addressing the long-term sustainability issues in the socioeconomic-ecological systems requires the resilience shift of non-state initiatives. Thus, non-state institutions must strengthen their resilience management capabilities by collaborating with other actors, networks, and institutions to promote sustainable development. This collaboration fosters societal understanding of these resilience factors, which are portrayed in this study. Finally, effective resource management necessitates a delicate balance between economic considerations and environmental preservation, supporting the sustainability of common resources. It is imperative to deepen our understanding of the interplay between the socioeconomic and ecological facets of these systems to ensure that our environmental laws serve as the proper framework for effective resource regulation and management.
Keywords: 330; Sustainability scheme; Social–ecological systems; Blue economy; Seafood; Inclusivity; Resilience; Non-state actors